Alterations in BCR heavy chain CDR3 repertoire characteristics in pediatric mycoplasma pneumoniae infection - Chen, Yanfei; Yuan, Yi; Liu, Xingzhu; Li, Bin; Meng, Lijuan; Xiao, Ying; Su, Zhongjian; Han, Linfei; Li, Hong; Deng, Lili; Li, Jun; Ye, Caixia; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionMycoplasma pneumoniae (MP) infection is a leading cause of pediatric pneumonia, triggering a complex immune response in which B cells play a critical role. This study aimed to analyze B cell receptor (BCR) heavy chain CDR3 repertoires in MP patients.MethodsClinical data from 202 children diagnosed with MP were retrospectively analyzed. Flow cytometry was used to assess B cell counts in 99 MP patients and 25 healthy controls (HC). Multiplex PCR was used to construct BCR heavy chain CDR3 repertoires from peripheral blood samples of 8 MP patients and 9 HC.ResultsSerological analysis revealed elevated levels of inflammatory markers, including C-reactive protein, interleukin-6, and ferritin, indicating an active immune response. Flow cytometry showed significantly increased B cell counts in MP patients compared to HC. Immunoglobulin levels were elevated in several patients, indicating immune fluctuations during infection. BCR repertoire analysis revealed increased diversity and altered clonotype distribution in MP patients, with preferential usage of IGHV1-18, IGHV7-4-1, and IGHJ6. MP patients exhibited a bimodal distribution of CDR3 lengths, with significantly longer CDR3 regions. Sixty-eight MP-exclusive clonotypes were identified, with evidence of clonal expansion.ConclusionThese findings suggest that alterations in the BCR heavy chain CDR3 repertoire play a crucial role in the immune response to MP infection and may offer insight into disease progression and therapeutic targets.